Empreendedorismo social e desenvolvimento sustentável: um estudo sobre a cadeia produtiva do babaçu no município de Itapecuru-Mirim - MA - Gomes, Bruna Caroline dos Santos (2022)
The present study has as its object of analysis lhe relationship between social entrepreneurship and the sustainable developraent of the babassu production chain from the specific case of the Itapccuru-Mirim region. It is shown lhat the exploitation of babassu in Maranhão took place in a complex and contradictory way, in which this fruit was mostly used only partially. While the industrial and commercial sectors accumulated surplus value, extractive families resold almonds by the kilo for a very low price. With the contribution of social movements in the countrysidc, in the carly 1990s, a discussion was opened about labor options that went beyond the formal relations of salaried work, with a more inclusive proposal, enterprises such as associations, cooperatives and mothers' clubs have spread. through the interior of Maranhão. In the Vale do Itapecuru region, coconut breakers, producers and entrcprencurs change the status quo through entrepreneurship. The investigation brings as a theoretical perspective the work of Alexander Chayanov, a Russian agrarian economist who investigated the specifics of the social fabric in rural areas. For the author, the salary phenomenon does not rcach the peasant production unit, which will have another motivation for work: the satisfaction of their needs through collective production, as occurs in the empirical field of the present research. In Itapecuru Mirim, we sought to characterize the role of social entrepreneurship and its contribution to the sustainable development of the babassu production chain in the region. It was also sought to assess whether this type of enterprise promotes the protagonism and empowerment of the families involved in the activity. In order to do so, field research and the application of questionnaires were used with agencies that support extractivism and family fanning that operatc in the region. It is conciuded about the relevance of social entrepreneurship as an income generator and in breaking some levei of social risk state in the investigated communities